Renewed Memory of Andrzej Niesiołowski and His Work In the Field of the Adult Learning Theory - Tadeusz Aleksander (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2016)
The book by Dominika Jagielska and Janina Kostkowicz Pedagogika humanizmu społecznego Andrzeja Niesiołowskiego (Pedagogy of social humanism of Andrzej Niesiołowski) (2015) poses a opportunity of reminding oneself of academic work of Andrzej Niesiołowski (1899-1945) in the field the theory of adult learning. The hero of the book was born and brought up in a patriotic family in Wielkopolska (Greater Poland, a Polish region). He graduated there, at the university of Poznan, and under the influence of prominent professors he developed his academic interests and passion for research. In a relatively short period of time he has written 15 books and over a 170 academic, popular science, and journalistic articles that cover the fields of sociology, pedagogy, social politics, and the adult learning theory. In his works he has presented himself as a representative of social humanism with personalist orientation. In his academic works in the field of the adult learning theory two prominent books stand out particularly: Formy i metody pracy oświatowej [Forms and methods of education] (1932), and Koła oświatowo-wychowawcze [Educational academic associations] (1939). In the former he characterized the institutions of extracurricular education in Poland and Europe that were the dominant ones during his lifetime. In the latter he described the self study movement (its genesis, development, and methodology) which was conducted in many countries in self study and educational academic associations. The essence of his reflection on education of adults understood in this way is the search for effective strategies of its development in order to desirably convert our country's social and economic structures.